Design and development of linear technology impact simulator test equipment / Shilawaty Abdul Mutalif - Abdul Mutalif, Shilawaty (2005)
This thesis is written to understand the design and development of the linear technology impact simulator test equipment. The thesis is a final year project for Faculty of Mechanical Engineering student and it is an industry-based project for PROTON. It is also project collaboration with Asian Autotec Sdn. Bhd. (ATEC). I have chosen Asian Autotec Sdn. Bhd. (ATEC) as my partner as they have given me the opportunity to explore design and develop linear technology impact simulator test equipment. My thesis starts with the understanding of linear impact simulator test equipment concept. In general, an impact test is a test for determining the energy absorbed in fracturing a test piece at high velocity. In studying linear impact simulator test equipment, the components consist of several parts that include the frame, base, structure, main bar and the secondary bar. Besides that, calculation required in the designing of linear impact simulator test equipment is also carried out. I use this calculation as a guide to design the linear technology impact simulator test equipment. After designing the linear technology impact simulator test equipment, development stage takes place. Development stage begins after the first testing was done in order to see whether the linear technology impact simulator test equipment has fulfilled the requirements given by PROTON. In this development stage, I change some of the initial design in order to achieve the objectives of this project. This stage was done with supervision of Asian Autotec Sdn. Bhd. and PROTON. Cost of the project is one of the main considerations during the designing and development stage. ATEC has given me the range of budget to work with and it must not exceed this budget